3D Phage-based biomolecular filter for effective high throughput capture of Salmonella Typhimurium in liquid streams. (April 2021) - Du, Songtao; Chen, I-Hsuan; MacLachlan, Alana; Liu, Yuzhe; Huang, Tung-shi; Cheng, Zhongyang; Chen, Pengyu; Chin, Bryan A.
Graphical abstract: Highlights: Filtration of foodborne pathogens with high capture rate and throughput. A 3D filter constructed by stacking ME filter elements under uniform magnetic field. 3D filter structuregenerates turbulence flow and improves capture performance. Abstract: Foodborne illnesses caused by pathogens on fresh produce remain one of the most critical food safety problems the world faces. The recalls of pasta salad in 2018 and pre-cut melons in 2019 imply current methods in identifying the source of pathogens and outbreak prevention are inappropriate and time consuming. In this article, a new technology, called the 3D phage-based biomolecular filter, was developed to simultaneously capture and concentrate foodborne pathogens from large volumes of liquid streams (food liquid or wash water streams). The 3D phage-based filter consisted of phage-immobilized magnetoelastic (ME) filter elements, a filter pipe system, and a uniform magnetic field to fix and align the ME filter elements in the 3D filter column. The closely packed ME filter elements display a 3D layered structure which allows for enhanced surface interaction of the immobilized bacteriophage with specific pathogens in the passing liquid streams. As a result, a pathogen capture rate of more than 90% was achieved at a high flow rate of 3 mm/s with 20, 000 ME filter elements. The capability of the 3D phage-based filter to capture pathogens in liquid streams at different filter element packing densities was further validated by experiments, finite element analysis and theoretical calculations. The capture rate increases significantly with larger numbers of ME filter elements placed in the testing pipe, and the turbulence flow induced by the 3D stacking of ME filter elements can further improve the capture efficiency. This technology enables rapid capture and analysis of large volume of water in processing fresh fruit and vegetables for the presence of small quantities of pathogens, which will ultimately benefit producers, the food industry, and society with improved food safety and production efficiency.